2019
DOI: 10.5812/zjrms.91408
|View full text |Cite
|
Sign up to set email alerts
|

Acute Pancreatitis in a Pregnant Women at 30 - 31 Weeks of Gestational Age with Complete Cure

Abstract: Introduction:Acute pancreatitis is an acute inflammatory disease of the pancreas characterized clinically by upper quadrant pain and elevated levels of enzymes in the blood. Although The pathogenesis of pancreatitis is not fully understood, gallstone and chronic alcohol abuse is considered for two-thirds or more cases in the united stated. Case Presentation: In this case report, the researchers present a 29-year-old pregnant female G3P2 with 31 w, 2 d of gestational age, who was referring to maternity ward wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In our study, 25% (8/32) of patients had an increase in serum amylase less than three times the normal value, and the increase in serum amylase was not related to the severity of APIP. Studies have shown that compared with serum amylase, serum lipase has a higher sensitivity and a larger diagnostic window [ 35 ]. In case of hyperlipidemic acute pancreatitis, lipase offers a better diagnostic accuracy (91.8%) than amylase (40.3%) [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 25% (8/32) of patients had an increase in serum amylase less than three times the normal value, and the increase in serum amylase was not related to the severity of APIP. Studies have shown that compared with serum amylase, serum lipase has a higher sensitivity and a larger diagnostic window [ 35 ]. In case of hyperlipidemic acute pancreatitis, lipase offers a better diagnostic accuracy (91.8%) than amylase (40.3%) [ 36 ].…”
Section: Discussionmentioning
confidence: 99%